All you need is … a network: The rise of interpretive public administration. (10th January 2022) - Bevir, Mark; Rhodes, R. A. W.
Abstract: For this 100th Anniversary issue of Public Administration, we review one of the more distinctive trends in the study of public administration—the rise of the interpretive approach. We tie interpretivism to an anti‐naturalist historicism and humanism in contrast to the formalism and scientism of mainstream public administration. We review developments in Britain, Western Europe, and the United States, concluding there is a divide between the empiricist Anglo‐Saxon approaches and Continental interpretive and critical approaches. We summarize Bevir and Rhodes' decentred approach with its focus on traditions, beliefs, practices, and dilemmas. We highlight its distinctive features compared with other interpretive approaches. We suggest the interpretive approach could develop further by blurring genres and practising bricolage. We conclude that interpretivism thrives in Britain and Continental Europe because there are established networks behind which lies the nineteenth century European tradition of hermeneutics and idealism.